2016
DOI: 10.20867/thm.22.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Indian reality tourism - a critical perspective

Abstract: Purpose -The purpose of this paper to find out the tangible potential and opportunities of realitytourism in India and other parts of the world. Do we expose our nudity, weaknesses and poverty to tourists or can it be used as an unconventional revenue source for local development of such backward areas? Design -The paper defines the concept of reality-tourism which is prevailing in India at a slow pace and provides a critical analyses about pros and cons of this type of tourism. It also analyses the view of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The study also suggested measures to ensure its sustainability. Gupta [75] identified the scope and trends of a niche tourism segment called Reality Tourism in India. The study discussed the potential benefits and negative consequences of promoting reality tourism in India.…”
Section: Develop Emerging Tourism Avenues and Change In Policiesmentioning
confidence: 99%
“…The study also suggested measures to ensure its sustainability. Gupta [75] identified the scope and trends of a niche tourism segment called Reality Tourism in India. The study discussed the potential benefits and negative consequences of promoting reality tourism in India.…”
Section: Develop Emerging Tourism Avenues and Change In Policiesmentioning
confidence: 99%
“…Note that the "three bottom lines" is a similar concept, in which all features must be larger than a given threshold [24]. Moreover, alternative tourism resembles geo-tourism, backpacking tourism, homestay (e.g., [31]), gastronomic tourism (e.g., [32]), cycling charity tourism (e.g., [33]), and reality tourism (e.g., [34]). Finally, the following tourism policies could be suggested for alternative tourism: recovery of ceremonies or craftsmanship, restoration of historical buildings or artistic sites, preservation of natural resources and of ancestral cultures, sharing of tourism revenues and access to resources, and relying on typical product-territory relationships such as olive oil or wine production.…”
Section: Sustainable Tourism (St): Maximizing Welfarementioning
confidence: 99%